2017
DOI: 10.1038/cddis.2017.276
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 derived carbon monoxide suppresses Aβ1–42 toxicity in astrocytes

Abstract: Neurodegeneration in Alzheimer’s disease (AD) is extensively studied, and the involvement of astrocytes and other cell types in this process has been described. However, the responses of astrocytes themselves to amyloid β peptides ((Aβ; the widely accepted major toxic factor in AD) is less well understood. Here, we show that Aβ(1-42) is toxic to primary cultures of astrocytes. Toxicity does not involve disruption of astrocyte Ca2+ homeostasis, but instead occurs via formation of the toxic reactive species, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 71 publications
0
36
0
1
Order By: Relevance
“…Aβ causes neuronal cell death in the development of AD, resulting in cognitive and behavioral deficits (28,29). The neuronal cell death is closely related to Aβ-induced oxidative stress and consequent activation of pro-apoptosis signaling, because antioxidative substances and inhibition of apoptosis signaling, alone or in combination, prevent the cell death (30)(31)(32). Astrocytes, a major glial cell type in the brain, participate in the neuropathogenic mechanisms after chronic exposure to Aβ (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aβ causes neuronal cell death in the development of AD, resulting in cognitive and behavioral deficits (28,29). The neuronal cell death is closely related to Aβ-induced oxidative stress and consequent activation of pro-apoptosis signaling, because antioxidative substances and inhibition of apoptosis signaling, alone or in combination, prevent the cell death (30)(31)(32). Astrocytes, a major glial cell type in the brain, participate in the neuropathogenic mechanisms after chronic exposure to Aβ (30).…”
Section: Discussionmentioning
confidence: 99%
“…The neuronal cell death is closely related to Aβ-induced oxidative stress and consequent activation of pro-apoptosis signaling, because antioxidative substances and inhibition of apoptosis signaling, alone or in combination, prevent the cell death (30)(31)(32). Astrocytes, a major glial cell type in the brain, participate in the neuropathogenic mechanisms after chronic exposure to Aβ (30). Aβ can activate astrocytes and then induce the release of inflammatory and neurotoxic molecules, contributing to chronic neuroinflammation and neuronal death (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hmox1, the inducible form of heme oxygenase, degrades heme to three products − ferrous ions, carbon monoxide, and biliverdin. In addition to this catalytic function in heme metabolism, Hmox1 may function as a cytoprotective factor through its end‐products with antioxidant, anti‐inflammatory, anti‐apoptotic, and cell‐signaling properties . Several studies have demonstrated the tissue protective properties of Hmox1 in mouse and rat models of cardiovascular, pulmonary, kidney, gastrointestinal, brain or skin injury, and disease .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, transient HO-1 upregulation by CORMs may be beneficial for AD therapies because several in vitro experiments demonstrate cytoprotective effects of CO. Treatment of astrocytes with CORM-2 suppresses the NOX-derived ROS caused by Aβ , which may be mediated by HO-1 induction [171]. CORM-2 can protect neurons from ROS-mediated apoptosis by inhibiting voltage-dependent K + (Kv) channels (i.e., Kv 2.1 ), which facilitates intracellular K + efflux as an initiating step in the apoptotic cascade [172].…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%